2001
DOI: 10.1054/bjoc.2000.1631
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of sequential chemotherapy with docetaxel after the weekly PELF regimen in advanced gastric cancer. A report from the Italian group for the study of digestive tract cancer

Abstract: SummaryIn advanced gastric cancer, we investigated feasibility and activity of sequential chemotherapy with docetaxel after an intensive weekly regimen consisting of cisplatin, epidoxorubicin, fluorouracil, leucovorin (PELF) plus filgrastim. Chemotherapy-naive patients with relapsed or metastatic gastric cancer received 8 weekly administrations of chemotherapy with cisplatin 40 mg/m 2 , fluorouracil 500 mg/m 2 ,epidoxorubicin 35 mg/m 2 , 6S-steroisomer of leucovorin 250 mg/m 2 and glutathione 1.5 g/m 2 . On th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…The overall response rate of 56% was within the range (30 -70%) of previous major protocols such as FAMTX, ELF, EAP, ECF, and recent taxane-based (Bokemeyer et al, 1997;Kollmannsberger et al, 2000;Cascinu et al, 2001) or irinotecan-based regimens (Bleiberg, 1999;Ajani et al, 2002;Slater et al, 2002). Recently, three other studies, using different administrating schedules of oxaliplatin and 5-FU, have also demonstrated a good efficacy in gastric cancer (Louvet et al, 2002;Kim et al, 2003;Al-Batran et al, 2004).…”
Section: Discussionsupporting
confidence: 66%
“…The overall response rate of 56% was within the range (30 -70%) of previous major protocols such as FAMTX, ELF, EAP, ECF, and recent taxane-based (Bokemeyer et al, 1997;Kollmannsberger et al, 2000;Cascinu et al, 2001) or irinotecan-based regimens (Bleiberg, 1999;Ajani et al, 2002;Slater et al, 2002). Recently, three other studies, using different administrating schedules of oxaliplatin and 5-FU, have also demonstrated a good efficacy in gastric cancer (Louvet et al, 2002;Kim et al, 2003;Al-Batran et al, 2004).…”
Section: Discussionsupporting
confidence: 66%
“…This same combination plus 5-FU shows similar activity [16]. In addition, a recent phase II trial considering the sequential application of docetaxel after PELF showed major objective responses, with manageable toxicity [17].…”
Section: Introductionmentioning
confidence: 79%
“…There is clear evidence that docetaxel has non-cross-resistant activity in advanced oesophagogastric cancer. Docetaxel has efficacy as a single agent after failure of platinum and fluoropyrimidines, as well as additive activity when used in combination with cisplatin and 5-FU (Cascinu et al, 2001;Van Cutsem et al, 2006). However, significant myelosuppression with 3-weekly administration poses a major problem for the development of combination chemotherapy regimens, because the myelosuppressive effects add to the toxicities of other chemotherapy agents.…”
Section: Discussionmentioning
confidence: 99%